Aminocarbonyl Fluorophores with a Strong Emissive Inverted Solvatochromism - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M; Martinez-Gomez, F; Morales-Lovera, S (American Chemical Society, 2024)
Three aminocarbonyls were synthesized, and their emissive spectral behavior recorded at various solvent polarities showed marked inverted solvatofluorochromism. The emission energy inversion occurs at moderate solvent polarities and was found to be triggered by a change in the solute-solvent interaction responsible for the stabilization of the highly zwitterionic excited state of the dyes, from dipolarity to acidity. © 2024 American Chemical Society.